2006
DOI: 10.1097/01.jcp.0000248603.76231.b7
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of Quetiapine Monotherapy in Bipolar I and II Depression

Abstract: This study evaluated the efficacy and tolerability of quetiapine monotherapy for depressive episodes in patients with bipolar I or II disorder (Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition) who were randomized to 8 weeks of double-blind treatment with quetiapine (300 or 600 mg/d; once daily, evening dosing) or placebo. Patients were assessed weekly using the Montgomery-Asberg Depression Rating Scale (MADRS) and Hamilton Depression Rating Scale (HAM-D). The primary end point was change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
166
2
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 467 publications
(180 citation statements)
references
References 35 publications
(34 reference statements)
9
166
2
3
Order By: Relevance
“…Pooled analyses of five identically designed trials demonstrated that quetiapine was superior to placebo, and moreover was equally effective for acute depression in BDI and BDII 243, 437. The latter finding must be reconciled with the fact that quetiapine beat placebo in only three of the five individual trials in patients with BDII, compared to all five in patients with BDI 253, 290, 438, 439, 440. This is probably because the smaller sample of BDII patients—only about half as many patients with BDII as BDI were enrolled in each of the trials—provided less statistical power for BDII.…”
Section: Bipolar II Disordermentioning
confidence: 99%
“…Pooled analyses of five identically designed trials demonstrated that quetiapine was superior to placebo, and moreover was equally effective for acute depression in BDI and BDII 243, 437. The latter finding must be reconciled with the fact that quetiapine beat placebo in only three of the five individual trials in patients with BDII, compared to all five in patients with BDI 253, 290, 438, 439, 440. This is probably because the smaller sample of BDII patients—only about half as many patients with BDII as BDI were enrolled in each of the trials—provided less statistical power for BDII.…”
Section: Bipolar II Disordermentioning
confidence: 99%
“…Among atypical antipsychotics, quetiapine monotherapy,11, 12 and olanzapine in combination with fluoxetine (OFC),13 have demonstrated efficacy in the acute treatment of bipolar depression, whereas aripiprazole monotherapy,14 and ziprasidone monotherapy15 and adjunctive therapy (with lithium or divalproex)16 were not significantly different from placebo in controlled acute trials. Quetiapine monotherapy17 and adjunctive therapy (with lithium or divalproex)18, 19, 20 demonstrated significant efficacy in preventing recurrence of both manic and depressive episodes in bipolar populations.…”
Section: Introductionmentioning
confidence: 99%
“…The NICE [16] and CANMAT [11] guidelines now recommend QTP as the first-line drug, especially for the more severe pathophysiology of acute mania, due to its rapid and potent antimanic effects. Meanwhile, the efficacy of QTP monotherapy in acute bipolar depression has been consistently confirmed by such double-blind, placebo-controlled studies as BOLDER (BipOLar DEpRession) I/II [8,20] and EMBOLDEN (Efficacy of Monotherapy SEROQUEL in BipOLar DEpressioN) I/II [17,21]. The latter EMBOLDEN studies also examined the efficacy of QTP monotherapy in relapse prevention for bipolar disorders, and the results suggested that the preventive effect of QTP monotherapy is superior to that of placebo for both manic and depressive recurrence, and is superior to that of Li for depressive recurrence [11], and that the efficacy of Li or VPA for relapse prevention of any mood episode is clearly augmented by QTP coadministration [10,22].…”
Section: Qtpmentioning
confidence: 85%
“…In fact, QTP, OLZ, ARI, RIS and paliperidone are known to have potent effects against acute mania as well as schizophrenia [6]. As for the treatment of acute bipolar depression, the efficacy of QTP monotherapy has been established [8], and OLZ exhibits similar efficacy when combined with fluoxetine (OLZ-fluoxetine combination: OFC) [9], both of which have been already approved by the FDA. In addition, it has been also confirmed that QTP [10,11], OLZ [7,11], ARI [5] and long-acting injection (LAI) of RIS [11] …”
Section: Practical Definition Of Mood Stabilizersmentioning
confidence: 99%